A support system for multiple perspectives knowledge management and conflict resolution. (1st January 2000) - Janssen, Terry; Sage, Andrew P.
This paper addresses the need for sound science, technology, and management assessment relative to policy decision-making, especially in areas that involve ecosystem health and sustainable development. It suggests an approach that involves a logical structure for evidence, a framed decision-making process, and an environment that encourages group participation. Toulmin-based logic possesses these characteristics and is used as the basis for development of the group decision support system described here. This system can support several user groups who can use the support system to state arguments for or against an important policy issue, and to assist in identifying and evaluating alternatives for implementation as policy decisions. The resulting decision support system assists in improving the clarity of the lines of reasoning used in specific situations; the warrants, grounds, and backings that are used to support claims and specific lines of reasoning; and the contradictions, rebuttals, and arguments surrounding each step in the reasoning process associated with evaluating a claim or counter-claim. Through use of this support system, experts and decision makers with differing views and backgrounds can better understand each other's thought processes in complex situations. The net effect is enhanced communications and understanding of the whole picture and, in many cases, consensus on decisions to be taken.